Hot Air as an Implicit Side Payment Arrangement: Could a Hot Air Provision have Saved the Kyoto-Agreement? - Urs Steiner Brandt; Gert Tinggaard Svendsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
The purpose of this paper is to analyse whether the presence of Hot Air trading jeopardizes the environmental target of an international environmental agree-ment. We argue that Hot Air can be used as an implicit side-payment mecha-nism to actually bring about higher environmental protection compared to the situation without the trade option. We point to the existence of a fundamental trade-off between costs of compliance and the creation of dynamic incentives to develop cheaper reduction technologies. Implicit side-payments, in terms of Hot Air provision, may be needed in order to establish a compromise between these opposing demands. We identify the shortcomings and benefits of allowing fully flexible permit trading including the allocation rule of grandfathering.
Keywords: Q28; H2; H4; 330; Hot Air; Global GHG trade; Kyoto protocol; Grandfathering; Cost issue; EU; US; Emissionshandel; Internationale Umweltpolitik; Klimaschutz; Welt